Control of Overhead Crane while Using Fuzzy Logic Dispatcher - Alavi Said Anaitollah; Y. N. Petrenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The objective of a crane control system is to ensure movement of a load with minimum load swing. A classical Proportional-Derivative (PID) controller is not the best solution of this problem due to the non-linear system. The paper presents a designing procedure of fuzzy logic controller on the basis of fuzzy logic and theory of a rough controller. Comparative indices of both controllers obtained as a result of digital modeling are given in the paper.